2011
DOI: 10.1007/978-1-61779-510-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Cuticle Refraction Microscopy: A Rapid and Simple Method for Imaging Drosophila Wing Topography, an Alternative Readout of Wing Planar Cell Polarity

Abstract: The polarity of hairs on the adult Drosophila wing provides information about the planar cell polarity (PCP) signaling events that occur during pupal wing development. We have recently shown that PCP signaling also determines the orientation of cuticle ridges that traverse the surface of the adult wing membrane; a feature we call the wing membrane topography. Although hair polarity is uniform across the wild-type wing, ridge orientation differs between the anterior and posterior wing. Consequently, mapping win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…For cases when it is hard to judge in which direction a hair points, it can be helpful to study the specimen in varying focal planes, and to compare with a sample with known polarity. For studying wing ridge polarity, as described by Collier and colleagues (Doyle et al, 2008; Hogan et al, 2011), cuticle refraction microscopy is useful (Neff et al, 2012). …”
Section: Mounting Of Adult Larval and Embryonic Tissue To Study Ommamentioning
confidence: 99%
“…For cases when it is hard to judge in which direction a hair points, it can be helpful to study the specimen in varying focal planes, and to compare with a sample with known polarity. For studying wing ridge polarity, as described by Collier and colleagues (Doyle et al, 2008; Hogan et al, 2011), cuticle refraction microscopy is useful (Neff et al, 2012). …”
Section: Mounting Of Adult Larval and Embryonic Tissue To Study Ommamentioning
confidence: 99%
“…To facilitate our studies of Drosophila wing topography, we developed a technique (CRM) that allows us to visualize Drosophila wing membrane ridges using light microscopy (Doyle et al 2008; Neff et al 2012). Using the CRM method, we found that membrane ridges are visible in light micrographs as bright lines against a dark background.…”
Section: Resultsmentioning
confidence: 99%
“…Our cuticle refraction microscopy (CRM) imaging protocol has been described in detail previously (Doyle et al 2008; Neff et al 2012). In brief, adult Drosophila wings were removed and laid gently on top of a thin layer of clear nail polish.…”
Section: Methodsmentioning
confidence: 99%